Investigating the expansion characteristics of geopolymer cement samples in a water bath and compared with the expansion of ASTM Class-G cement - Abd Rahman, Siti Humairah Bt (ELSEVIER SCI LTD, 2020)
In selecting the binder composition for oil well application, its stability is an important design parameter. This paper presents the results of an experimental study conducted for comparing the linear expansion characteristics of geopolymer cement with the traditionally used ASTM Class G cement system. The expansion test was done in a water bath at 60 degrees C subjected to different curing intervals. The linear expansion of a cement system defines as the dimensional changes occur in the system, which is sometimes required to avoid the cement shrinkage during the hydration phase. In the case when the desired level of expansion is not achieved in the system, then the commercially available expandable materials are added in the class G cement system that enables the system to expand to the desired level. Shrinkage in the cementing system causes the formation of a microannulus or induces a gap that may allow the migration of fluid, hence the integrity of the system could be lost. This experimental study has revealed that the geopolymer cement tends to expand 0.15%-0.2% without the addition of any admixture, whereas the ASTM Class G cement has shown a lower value of linear expansion, which was obtained less than 0.1% after 18 days of curing. In the case of Class G cement, the addition of expandable material helped to increase the expansion; in the case of a geopolymer system, the additive has further accelerated the expansion.